Sense of Responsibility as an Important Component of Personality’s Psychosocial Maturity - Zakharyan, Eleonora (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
There are two main types of responsibility (locus control) in psychology. In case of the first one the personality is fully responsible for everything that happens to him (internal). In case of the second one the personality does not feel responsible for good or bad things that happen to him but blames other people (external). The studies discussed in our article prove that people with internal locus control are more confident, famous and predictable. People with external locus control are unprincipled; don't try to act appropriate to their group norms and cultural values. There is a positive correlation between internal locus control and meaning of life.
Keywords: responsibility, personal maturity, development, psychological age, locus control, internal, external, attribution, cognitive dissonance